Continuous, intrinsic magnetic depletion of erythrocytes from whole blood with a quadrupole magnet and annular flow channel; pilot scale study. Issue 6 (13th March 2018) - Moore, Lee R.; Mizutani, Daichi; Tanaka, Tomoya; Buck, Amy; Yazer, Mark; Zborowski, Maciej; Chalmers, Jeffrey J.
Abstract: The ability to separate RBCs from the other components of whole blood has a number of useful clinical and research applications ranging from removing RBCs from typical clinical blood draw, bone marrow transplants to transfusions of these RBCs to patients after significant blood loss. Viewed from a mechanistic/process perspective, there are three routine methodologies to remove RBCs: 1) RBCs lysis, 2) separation of the RBCs from the nucleated cells (i.e., stem cells) based on density differences typically facilitated through centrifugation or sedimentation agents, and 3) antibody based separation in which a targeted RBC is bound with an affinity ligand that facilitates its removal. More recently, several microfluidic based techniques have also been reported. In this report, we describe the performance of continuous RBC separation achieved by the deflection of intrinsically magnetic, deoxygenated RBCs as they flow through a magnetic energy gradient created by quadrupole magnet. This quadrupole magnetic, with aperture of 9.65 mm, has a maximum field of B 0  = 1.36 T at the pole tips and a constant field gradient of B 0 / r 0  = 286 T/m. The annular flow channel, contained within this quadrupole magnet, is 203 mm long, has an inner radius of 3.98 mm, and an inner, outer radius of 4.36 mm, which corresponds to an annulus radius of 380 micrometer. At the entrance and exit to this annular channel, a manifold was designed which allows a cell suspension and sheath fluid to be injected, and a RBC enriched exit flow (containing the magnetically deflected RBCs) and a RBC depleted exit flow to be collected. Guided by theoretical models previously published, a limited number of operating parameters; total flow rate, flow rate ratios of flows in and flow out, and ratios of RBC to polystyrene control beads was tested. The overall performance of this system is consistent with our previously presented, theoretical models and our intuition. As expected, the normalized recovery of RBCs in the RBC exit fraction ranged from approximately 95% down to 60%, as the total flow rate through the system increased from 0.1 to 0.6 ml/min. At the cell concentrations studied, this corresponds to a flow rate of 1.5 × 10 6 –9 × 10 6  cells/min. While the throughput of these pilot scale studies are slow for practical applications, the general agreement with theory, and the small cross‐sectional area in which the actual separation is achieved, 77 mm 2 (annulus radius times the length), and corresponding volume of approximately 2 mls, suggests the potential to scale‐up a system for practical applications exists and is actively being pursued. Abstract : Cross sectional field heat map calculated midway down the length of the QMS magnet, left, and 3‐D isometric view of the QMS magnet, rightX.